Argumentation in actual practice : topical studies about argumentative discourse in context - Eemeren, F. H. van (Frans Hendrik), 1946-; Garssen, Bart (John Benjamins Publishing Company, 2019)
"Argumentation in Actual Practice contains a collection of topical studies about argumentative discourse in context written by argumentation scholars from a diversity of academic backgrounds. Some contributions provide general perspectives, other contributions deal with specific issues, particular types of argumentative discourse or individual argumentative speech events. The contexts in which argumentation is examined vary from politics and the media to medical, juridical, educational, commercial or military contexts, a specific academic discipline, a special issue or pertain to all kinds of contextualised argumentative discourse. The issues discussed include the interpretation and analysis of argumentation, strategic manoeuvring, argument schemes, the stock issues, the fallacies, the principle of charity and the persuasiveness of argumentative discourse. A common feature is that they are all empirically-oriented and that virtually all of them are strongly concerned with an adequate understanding of contextualised argumentative discourse and the factors that may increase or decrease its reasonableness and effectiveness"-- Provided by publisher.
Keywords: Persuasion (Rhetoric) -- Congresses.; Discourse analysis -- Congresses.; LANGUAGE ARTS & DISCIPLINES / Rhetoric.; Discourse analysis; Persuasion (Rhetoric); Conference papers and proceedings